Pengaruh Gaya Kepemimpinan, Kemampuan Me-Manage Stres Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening (Studi Pada Kantor Kekayaan Negara & Lelang Kanwil Banten) - Siti Nuri Nila Sari; Wawan Prahiawan; Mahdani; Ranthy Pancasasti (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2021)
The purpose of this study was to examine the ability to manage work stress on employee performance, the effect of ability to manage work stress on job satisfaction, the effect of leadership style on job satisfaction, the effect of job satisfaction on employee performance, the effect of ability to manage work stress on job satisfaction, the effect in kpknl djkn banten. The population in this study is government employees at kpknl djkn banten. And the number that will be as a sample of the entire population is 102. The results of this study indicate that there is a significant effect of ability to manage work stress on employee performance, there is a significant effect of ability to manage work stress on job satisfaction, there is a significant effect of leadership style on job satisfaction, there is a significant effect of job satisfaction on employee performance.